The inverse problem of acoustic diagnosis for three-dimensional media - Goncharsky, A.V.; Romanov, S.Y.; Kharchenko, S.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2006)
A specific form of the uncertainty constant for Meyer’s wavelet is derived. This form is considered as a functional dependent on the function specifying Meyer’s wavelet family. Numerical minimization of this functional allows us to find an expression for the wavelet whose uncertainty constant is less than the standard one by a factor of 1.5.